PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Adinda Ramandani; Andi Rahman; Maharani Oktavia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of 5th grade students in science at SD Negeri 74 Palembang, which is caused by the implementation of a less diverse and teacher-centered learning approach, which is the main driver of this research. The purpose of this study is to determine how the discovery learning model affects the learning outcomes of 5th grade students in science. By using a pretest-posttest control group design and a quasi-experimental design, this research methodology is quantitative. A total of 124 5th grade students from SD Negeri 74 Palembang are the research population, and 58 are the research sample, namely 27 students from the experimental class and 31 from the control class. Essay tests in the form of pretest and posttest are used as a data collection approach. The discovery learning model is used to handle the experimental class, while traditional learning is applied to the control group. The average posttest score for the experimental class is 80.07 which is higher than the average pretest score of 65.77 according to the data. By encouraging students to freely discover topics through conversations and problem-solving exercises, the discovery learning model can foster more active and creative learning. The results of the science learning of fifth grade students at SD Negeri 74 Palembang are influenced by the discovery learning model according to the results of data analysis.Keywords: discovery learning, learning outcomes, science, elementary school